Studi Fenomenologi Tentang Peran Chatgpt Dalam Proses Belajar Mahasiswa Di Universitas Yudharta Pasuruan - Naura Sholhub Arasyidiah; Moh. Edi Marzuki (4, 2025)
This study aims to deeply understand the experiences of students at Yudharta University, Pasuruan, in using ChatGPT as part of their learning process. The approach used was qualitative, with a phenomenological approach, focusing on students' subjective meanings and experiences in interacting with artificial intelligence (AI)-based digital media. ChatGPT was chosen as the primary object of study because it has become a significant learning medium among students, helping them understand course material, complete academic assignments, and develop scientific arguments. The research findings indicate that ChatGPT impacts three main aspects: cognitive (influencing how students access and process information), affective (causing anxiety when access is disrupted), and behavioral (reducing manual reading activities and increasing dependence on technology). The use of ChatGPT also raises ethical dilemmas, such as covert plagiarism and a decline in academic honesty. Within the context of Media Dependency Theory, students demonstrate a high level of dependence on ChatGPT, especially under conditions of academic pressure and a lack of manual digital literacy. This research recommends the need for regulations and internal campus communication strategies regarding the use of AI in academic activities, to maintain the quality of learning and scientific ethics. The results of this study are expected to contribute to the development of communication science, particularly in the study of human interaction with AI-based digital media. Abstrak Penelitian ini bertujuan untuk memahami secara mendalam pengalaman mahasiswa Universitas Yudharta Pasuruan dalam menggunakan ChatGPT sebagai bagian dari proses belajar mereka. Pendekatan yang digunakan adalah kualitatif dengan jenis penelitian fenomenologi, yang berfokus pada makna subjektif dan pengalaman mahasiswa dalam berinteraksi dengan media digital berbasis kecerdasan buatan (AI). ChatGPT dipilih sebagai objek utama karena telah menjadi media belajar yang signifikan di kalangan mahasiswa, baik dalam membantu memahami materi kuliah, menyelesaikan tugas akademik, maupun membangun argumentasi ilmiah. Temuan penelitian menunjukkan bahwa ChatGPT memberikan dampak pada tiga aspek utama yaitu: kognitif (memengaruhi cara mahasiswa mengakses dan memproses informasi), afektif (menimbulkan kecemasan saat akses terganggu), dan perilaku (mengurangi aktivitas membaca manual dan meningkatkan ketergantungan terhadap teknologi). Penggunaan ChatGPT juga menimbulkan dilema etika, seperti plagiarisme terselubung dan penurunan kejujuran akademik. Dalam konteks teori ketergantungan media (Media Dependency Theory), mahasiswa menunjukkan tingkat ketergantungan yang tinggi terhadap ChatGPT, terutama dalam kondisi tekanan akademik dan minimnya literasi digital manual. Penelitian ini merekomendasikan perlunya regulasi dan strategi komunikasi internal kampus terkait penggunaan AI dalam kegiatan akademik, guna menjaga kualitas pembelajaran dan etika ilmiah. Hasil studi ini diharapkan dapat memberikan kontribusi terhadap pengembangan ilmu komunikasi, khususnya dalam kajian interaksi manusia dengan media digital berbasis AI.